Ainsliaea fragrans champ. Extract prevents cervicitis in BALB/c mice and regulates MyD88-NF-κB signaling pathway in MALP-2-stimulated RAW264.7 cells. (6th April 2021) - Lin, Xiaobing; An, Xiaofei; Wang, Lingling; Zhang, Junhan; Abuduwaili, Abudusaimi; Wang, Hao; Yan, Ming
Abstract: Ethnopharmacological relevance Ainsliaea fragrans Champ. (A. fragrans) is used to treat infection of the lower genital tract in gynecology, such as cervicitis and pelvic inflammatory disease. This study analyzed the therapeutic efficiency of A. fragrans on cervicitis and the inhibition mechanism of AF-p2 in MALP-2-stimulated RAW264.7 cells. Materials and methods The anti- Ureaplasma urealyticum (Uu) activity of A. fragrans and AF-p2 were determined by antimicrobial susceptibility testing. The activity of A. fragrans extracts (AFext) was evaluated in female BALB/c mice with cervicitis induced by Uu. Furthermore, the therapeutic mechanism of AFext and AF-p2 on myeloid differentiation factor 88 (MyD88) pathway were studied in macrophage activating lipopeptide-2 (MALP-2) irritated RAW264.7 cells. Results AFext could suppress the proliferation of Uu in vitro, including the azithromycin resistant strains. Meanwhile, AFext prevented cervicitis caused by Uu infection in BALB/c mice. Moreover, both AFext and AF-p2 could significantly suppress the nitric oxide (NO) production as well as other proinflammatory cytokines (IL-1β, IL-6, TNF-α) in MALP-2 stimulated RAW264.7 cells. Moreover, AF-p2 also down-regulated iNOS, p65, Iκ-Bα, MyD88 and cyclooxygenase-2 (COX-2) levels in RAW264.7 cells. Conclusion This study indicated that AFext had a therapeutic effect in cervicitis induced by Uu infection. Furthermore, the lead compound AF-p2 showed an anti-infectious effect in MALP-2 irritated RAW264.7 cells through downregulating MyD88-NF-κB signaling pathway. Graphical abstract: Image 1